Transesterification Of Crude Palm Oil To Fatty Acid Methyl Esters (FAME) Mediated By Lipase In Batch And Continuous Systems - Sim , Jia Huey (2011)
The rapid increase in the crude oil prices due to diminishing reserves of fossil fuels and the increased rate of world energy consumption have drawn attention of the researchers towards biodiesel as an alternative energy source. The transformation of palm oil into value-added product biodiesel can help to increase its commercial value of palm oil. The green technology of enzymatic transesterification with crude palm oil (CPO) as feedstock for biodiesel production has been studied in the present research.